2017
DOI: 10.1016/j.jpba.2017.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a quantification method for cucurbitacins E and I in rat plasma: Application to population pharmacokinetic studies

Abstract: Cucurbitacin E is a potential drug candidate due to its anticancer activity, recognition of its molecular targets, and synergism with other drugs used for cancer treatment. However, the use of cucurbitacin E in clinical practice is not possible because of important knowledge gaps in its preclinical and clinical pharmacokinetic characteristics. Cucurbitacin E is hydrolyzed to cucurbitacin I in plasma and in human liver microsomes. The aim of this study was to evaluate the population pharmacokinetics of cucurbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is very important to understand the in vivo pharmacological properties of any natural compound through in-depth understanding of drug metabolism and pharmacokinetics. The pharmacokinetic results showed that CE (1 mg/kg) was administered intravenously to male Wistar rats with a release time of 0.45 h, clearance of 4.13 L/h, and elimination half-life of 4.57 h . While no data currently exist on the pharmacokinetic profile of oral or intraperitoneal administration of CE in vivo, studies have demonstrated that the priority of the bioavailability was intravenous injection, intraperitoneal injection, and oral administration .…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to understand the in vivo pharmacological properties of any natural compound through in-depth understanding of drug metabolism and pharmacokinetics. The pharmacokinetic results showed that CE (1 mg/kg) was administered intravenously to male Wistar rats with a release time of 0.45 h, clearance of 4.13 L/h, and elimination half-life of 4.57 h . While no data currently exist on the pharmacokinetic profile of oral or intraperitoneal administration of CE in vivo, studies have demonstrated that the priority of the bioavailability was intravenous injection, intraperitoneal injection, and oral administration .…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC apparatus was equipped with quaternary pump, autosampler, and UV detector (Jasco, Japan). The separation of cucurbitacins was achieved on Hiber C18 column (250x4.6 mm, 5 μm) and using published protocol with minor modifications 48 . The mobile phase with solvents acetonitrile, water and methanol (32:35:33, v/v/v) was used.…”
Section: Steam Bath Assisted Extraction (Sbae) Sbae Was Carried On Amentioning
confidence: 99%
“…Compared with the content in the experimental group, more metabolites found in the control group metabolites are mostly intermediate metabolites of various biochemical reactions, such as 2-hydroxy-2-glutaric acid is the pentose phosphate intermediate [ 8 ], chlorinated acid cyclohexylamine is cyclohexylamine-generated intermediate [ 9 ], and l-methylinosine is the center of the cancer carbon metabolites [ 7 , 10 – 12 ]. If these products are not eliminated in time, there will be some harm to the human body.…”
Section: Discussionmentioning
confidence: 99%